PENGARUH STATUS SOSIAL EKONOMI DAN POLA ASUH ORANG TUA TERHADAP PRESTASI BELAJAR SISWA: Survei pada siswa kelas XI IPS SMA Plus Assalaam Bandung Tahun Ajaran 2022/2023 - Gustari, Zetira Dwi; Setiani, Ani; S, Yudho Ramafrizal (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This writing aims to find out: (i) Is there an effect of socio-economic status on student achievement in class XI IPS SMA Plus Assalaam, (ii) Is there an effect of parenting style on student achievement in class XI IPS SMA Plus Assalaam, (iii) How big is the influence of socioeconomic status and parenting style on student achievement in class XI IPS SMA Plus Assalaam. This study used a survey method with a quantitative approach and data collection techniques in the form of a questionnaire. The results showed: (i) There was a significant effect of X1 on Y, the magnitude of the effect was 0.0023% on SE and 0.00116% on SR, (ii) There was an influence of X2 on Y which was significant, the amount of influence was as much as 1.9877% in SE and 0.99884% in SR, (iii) The amount of contribution given by X1 and X2 is 0.020 or equal to 2%. Based on this research, there is an influence of 2%, which means that 98% is influenced by other variables. Suggestions from the author: (i) for students, to know how much influence parents have on learning achievement, (ii) for parents, to help guide children in educational development, (iii) for schools, to consider improving learning achievement, (iv) for the community, it can provide information to the public on factors that can affect learning achievement, (v) for future researchers, it can find other variables that can influence it.